BDNF and its Role in the Alcohol Abuse Initiated During Early Adolescence: Evidence from Preclinical and Clinical Studies - Cutuli, Debora; Sampedro-Piquero, Piquero (Current Neuropharmacology, 2022)
Brain-derived neurotrophic factor (BDNF) is a crucial brain signaling protein that is integral to many signaling pathways. This neurotrophin has shown to be highly involved in brain plastic processes such as neurogenesis, synaptic plasticity, axonal growth, and neurotransmission, among others. In the first part of this review, we revise the role of BDNF in different neuroplastic processes within the central nervous system. On the other hand, its deficiency in key neural circuits is associated with the development of psychiatric disorders, including alcohol abuse disorder. Many people begin to drink alcohol during adolescence, and it seems that changes in BDNF are evident after the adolescent regularly consumes alcohol. Therefore, the second part of this manuscript addresses the involvement of BDNF during adolescent brain maturation and how this process can be negatively affected by alcohol abuse. Finally, we propose different BNDF enhancers, both behavioral and pharmacological, which should be considered in the treatment of problematic alcohol consumption initiated during the adolescence.
Keywords: neuroplasticity